Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, \(x^2-25-\left(x+5\right)=0\)
\(\Rightarrow x^2-5^2-\left(x+5\right)=0\)
\(\Rightarrow\left(x-5\right)\times\left(x+5\right)-\left(x+5\right)=0\)
\(\Rightarrow\left(x+5\right)\times\left(x-5-1\right)=0\)
\(\Rightarrow\left(x+5\right)\times\left(x-6\right)=0\)
\(\Rightarrow\hept{\begin{cases}x+5=0\\x-6=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=0-5=\left(-5\right)\\x=0+6=6\end{cases}}\)
b, \(\left(2x-1\right)^2-\left(4x^2-1\right)=0\)
\(\Rightarrow\left(2x-1\right)^2-\left(\left(2x\right)^2-1^2\right)=0\)
\(\Rightarrow\left(2x-1\right)^2-\left(2x-1\right)\times\left(2x+1\right)=0\)
\(\Rightarrow\left(2x-1\right)\times\left(2x-1-\left(2x+1\right)\right)=0\)
\(\Rightarrow\left(2x-1\right)\times\left(2x-1-2x-1\right)=0\)
\(\Rightarrow\left(2x-1\right)\times\left(-2\right)=0\)\(\Rightarrow\left(-4x\right)+2=0\)
\(\Rightarrow\left(-4x\right)=0-2=-2\)
\(\Rightarrow x=\frac{-2}{-4}=\frac{1}{2}\)
c, \(x^2\times\left(x^2+4\right)-x^2-4=0\)
\(\Rightarrow x^2\times\left(x^2+4\right)-\left(x^2+4\right)=0\)
\(\Rightarrow\left(x^2-1\right)\times\left(x^2+4\right)=0\)
\(\Rightarrow\hept{\begin{cases}x^2-1=0\\x^2+4=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x^2=1\\x^2=\left(-4\right)\end{cases}}\)
\(\Rightarrow x=1\)
\(4x^2-28=0\)
\(\Leftrightarrow4\left(x^2-7\right)=0\)
\(\Leftrightarrow x^2-7=0\)
\(\Leftrightarrow x^2=7\)
\(\Leftrightarrow x=\pm\sqrt{7}\)
\(x^2-3x=0\)
\(\Leftrightarrow x\left(x-3\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x-3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
\(x^5-9x=0\)
\(\Leftrightarrow x\left(x^4-9\right)=0\)
\(\Leftrightarrow\orbr{\begin{cases}x=0\\x^4-9=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=\pm\sqrt[4]{9}\end{cases}}\)
MATH ERROR
0 .